Stop him-mass action rally, 12:30 Cowell - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Santa Cruz:::University place::::::::::::
Silk screen print shows the face of President Nixon situated atop two bones in an X shape. The image is a reproduction of the skull and crossbones sign for poison. The words "STOP HIM" are written on top and "MASS ACTION RALLY 12:30 COWELL" are at the bottom.